P17.04.B Combination of Trofosfamide and Etoposide in Recurrent Glioma. (5th September 2022) - Schmidt, T; Agkatsev, S; Feldheim, J; Oster, C; Blau, T; Sure, U; Keyvani, K; Kleinschnitz, C; Stuschke, M; Hermann, K; Deuschl, C; Scheffler, B; et al.
Abstract: Background: Disease relapse almost inevitably occurs in patients with adult-type diffuse glioma. Standard of care treatment options at tumor relapse are still not well defined. Frequently used drugs for adult-type diffuse glioma recurrence include lomustine (CCNU) and bevacizumab. Few studies indicate that the combination of trofosfamide/etoposide, given their high lipid solubility with good blood-brain barrier penetrance, may be feasible in pediatric glioblastoma patients. In this retrospective analysis, we determined tolerability and feasibility of combined trofosfamide/etoposide treatment at disease recurrence of patients with adult-type diffuse glioma. Material and Methods: We collected clinicopathological data from adult patients with adult-type diffuse glioma treated with the combination of trofosfamide/etoposide at the Division of Clinical Neurooncology at the University Hospital Essen. Only those patients were considered eligible who received trofosfamide/etoposide treatment for more than four weeks (one course). Trofosfamide (100mg/m 2 /day) and Etoposide (25mg/m 2 /day) was administered orally in a "one week on, one week off" scheme. A cohort of patients receiving empiric treatment at the investigators' discretion balanced for tumor entity and canonical prognostic factors (number of previous treatments, MGMT promoter methylation, IDH mutation status, KPS, age, extent of resection) served as control. We collected toxicity data as it pertained to CTCAE (Common Terminology Criteria for Adverse Events, version 5.0) and survival data to explore putative efficacy. Results: A total of 33 patients were eligible for this analysis. In the IDH wild-type glioblastoma (n=18) subgroup, median progression-free survival (3.8 months versus 2.9 months, HR: 2.09, 95% CI: 1.010-4.312, p =0.0227; PFS-6: 39% versus 6%) and median overall survival (10.4 months versus 5.7 months, HR: 3.05, 95% CI: 1.393-6.655, p =0.0008) were significantly prolonged as compared to the control cohort. In a multivariable Cox regression analysis, treatment with trofosfamide/etoposide emerged as statistically significant prognostic marker regarding progression-free survival and overall survival. We observed high-grade adverse events (CTCAE grade≥III ) in 21 (64%) of all recurrent glioma patients with hematotoxicity comprising most adverse events ( n =18, 86%). Lymphopenia was by far the most observed hematotoxic adverse event ( n =13, 62%). Among non-hematologic high-grade adverse events was transaminase elevation ( n =3, 14%). Conclusion: This study provides first indication that the combination of trofosfamide/etoposide is safe in patients with adult-type diffuse gliomas and may be associated with prolonged survival in adult patients with recurrent IDH wildtype glioblastoma. Our data provide a reasonable rationale for follow-up of a larger cohort in a prospective controlled trial.